Specific behaviour, mood and personality traits may contribute to obesity in patients with craniopharyngioma. (18th July 2014) - Roemmler‐Zehrer, J.; Geigenberger, V.; Störmann, S.; Ising, M.; Pfister, H.; Sievers, C.; Stalla, G.K.; Schopohl, J.
Summary Introduction Patients with craniopharyngioma (CP) often suffer from obesity, but the underlying causes are still not fully understood. We compared CP to patients with nonfunctioning pituitary adenoma (NFPA) and to a control group (CG) using standardized questionnaires to investigate whether behavioural, mood or personality traits contribute to obesity. Methods We compared 31 patients with CP (42% male, 53 ± 15·1 years) to 26 patients with NFPA (71% male, 63·2 ± 10·3 years) and to age‐ and gender‐matched local CG (ratio 2:1). Normative data from the literature are included for reference. Patients were asked to complete eleven standardized questionnaires. Two questionnaires were used to evaluate eating disorders (FEV, EDE‐Q), one depression (BDI), one anxiety (STAI), three health‐related quality of life (SF‐36, EuroQoL, QoL‐AGHDA), one sleepiness (Epworth Sleepiness Scale), two personality (EPQ‐RK, TPQ) and one body image (FKB‐20). Results Patients with CP scored significantly higher in conscious hunger perception (FEV, CP 5·8 ± 3·2 scores, NFPA 3·6 ± 3·3 scores, CG 3·0 ± 2·5, P < 0·001). They had similar scores for BDI compared with NFPA, but higher scores to CG (P < 0·001, CP 10·6 ± 8·3, NFPA 7·5 ± 5·7, CG 4·96 ± 4·2). CP and NFPA scored higher than CG for anxiety and personality traits such as harm avoidance, fatigability and asthenia and slightly higher for neuroticism. No differences were seen for EDE‐Q, quality of life, daytime sleepiness and body image between CP and NFPA. However, differences could be observed to normative data from the literature. Conclusion Obesity in patients with CP might be influenced by eating disorders, negative mood alterations and increased anxiety‐related personality traits.